Flow Injection Spectrophotometric Technique for Determining of Genistein in Pure and Supplements Formulations Through Diazotization Coupling Reaction - F.Mohammed, Farqid; Subhi Abed, Sadeem Subhi Abed (Iraqi Journal of Pharmaceutical Sciences, 2022)
Genistein (GEN) is The major isoflavone found in soybeans, has a number of cardiovascular health benefits, Postmenopausal syndrome and osteoporosis. A direct flow injection analysis method for estimation of (GEN) in pure and supplements formulation . This system is based on diazotization coupling reactions between procaine penciline (PR) and genistein in basic medium, they formed yellow dyes have maximum absorption at 416 nm. Calibration curve were constructed over different GEN concentrations, linearity for GEN was 10-100 µg.mL-1 and detection limits of 1.51 ?g/mL. In the FIA technique, all analytical factors were analyzed and optimized. The established method was successfully used to determine GEN in the formulations of its supplement